Metabolite profiling of Trichinella spiralis adult worms and muscle larvae identifies their excretory and secretory products - Uthailak, Naphatsamon; Adisakwattana, Poom; Chienwichai, Peerut; Tipthara, Phornpimon; Tarning, Joel; Thawornkuno, Charin; Thiangtrongjit, Tipparat; Reamtong, Onrapak (Frontiers in Cellular and Infection Microbiology, 2023)
Human trichinellosis is a parasitic infection caused by roundworms belonging to the genus Trichinella, especially Trichinella spiralis. Early and accurate clinical diagnoses of trichinellosis are required for efficacious prognosis and treatment. Current drug therapies are limited by antiparasitic resistance, poor absorption, and an inability to kill the encapsulating muscle-stage larvae. Therefore, reliable biomarkers and drug targets for novel diagnostic approaches and anthelmintic drugs are required. In this study, metabolite profiles of T. spiralis adult worms and muscle larvae were obtained using mass spectrometry-based metabolomics. In addition, metabolite-based biomarkers of T. spiralis excretory–secretory products and their related metabolic pathways were characterized. The metabolic profiling identified major, related metabolic pathways involving adenosine monophosphate (AMP)-dependent synthetase/ligase and glycolysis/gluconeogenesis in T. spiralis adult worms and muscle larvae, respectively. These pathways are potential drug targets for the treatment of the intestinal and muscular phases of infection. The metabolome of larva excretory–secretory products was characterized, with amino acid permease and carbohydrate kinase being identified as key metabolic pathways. Among six metabolites, decanoyl-l-carnitine and 2,3-dinor-6-keto prostaglandin F1α-d9 were identified as potential metabolite-based biomarkers that might be related to the host inflammatory processes. In summary, this study compared the relationships between the metabolic profiles of two T. spiralis growth stages. Importantly, the main metabolites and metabolic pathways identified may aid the development of novel clinical diagnostics and therapeutics for human trichinellosis and other related helminthic infections.